Performance of the 2019 EULAR/ACR classification criteria for systemic lupus erythematosus in early disease, across sexes and ethnicities. Issue 10 (14th August 2020) - Johnson, Sindhu R; Brinks, Ralph; Costenbader, Karen H; Daikh, David; Mosca, Marta; Ramsey-Goldman, Rosalind; Smolen, Josef S; Wofsy, David; Boumpas, Dimitrios T; Kamen, Diane L; Jayne, David; Cervera, R; et al.
Abstract : Objectives: The European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) 2019 Classification Criteria for systemic lupus erythematosus (SLE) have been validated with high sensitivity and specificity. We evaluated the performance of the new criteria with regard to disease duration, sex and race/ethnicity, and compared its performance against the Systemic Lupus International Collaborating Clinics (SLICC) 2012 and ACR 1982/1997 criteria. Methods: Twenty-one SLE centres from 16 countries submitted SLE cases and mimicking controls to form the validation cohort. The sensitivity and specificity of the EULAR/ACR 2019, SLICC 2012 and ACR 1982/1997 criteria were evaluated. Results: The cohort consisted of female (n=1098), male (n=172), Asian (n=118), black (n=68), Hispanic (n=124) and white (n=941) patients; with an SLE duration of 1 to <3 years (n=196) and ≥5 years (n=879). Among patients with 1 to <3 years disease duration, the EULAR/ACR criteria had better sensitivity than the ACR criteria (97% vs 81%). The EULAR/ACR criteria performed well in men (sensitivity 93%, specificity 96%) and women (sensitivity 97%, specificity 94%). Among women, the EULAR/ACR criteria had better sensitivity than the ACR criteria (97% vs 83%) and better specificity than the SLICC criteria (94% vs 82%). Among white patients, the EULAR/ACR criteria had better sensitivity than the ACR criteria (95% vs 83%) and better specificity than the SLICC criteria (94% vs 83%). The EULAR/ACR criteria performed well among black patients (sensitivity of 98%, specificity 100%), and had better sensitivity than the ACR criteria among Hispanic patients (100% vs 86%) and Asian patients (97% vs 77%). Conclusions: The EULAR/ACR 2019 criteria perform well among patients with early disease, men, women, white, black, Hispanic and Asian patients. These criteria have superior sensitivity than the ACR criteria and/or superior specificity than the SLICC criteria across many subgroups.